Efficiency of culture-based fisheries production in village irrigation systems of Sri Lanka. Issue 1 (2nd January 2019) - Kularatne, Mohottala G.; Pascoe, Sean; Wilson, Clevo; Robinson, Tim
Abstract: Despite the growing popularity of culture-based fisheries (CBFs) associated with village irrigation systems (VISs) in Sri Lanka, there is less knowledge about factors that influence productivity levels. CBFs compete with rice for access to water in the VIS, so maximizing the efficiency of CBFs is essential to ensure that the limited water resources are used most effectively. To address this, primary data from 325 fish farming groups were used to estimate a stochastic translog production frontier. Technical efficiency in these irrigation systems was found to be generally low, and substantially lower than that of other aquaculture production systems in other Asian countries. This suggests that production can be increased substantially with better management using existing technology and resources. Removing subsidies, improving consultation with extension officials and improving water user rights – in particular, the introduction of a transferable community quota system – were found to be key means for improving efficiency.